2022
DOI: 10.3389/fcvm.2022.1017505
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of underlying diseases in syncope and treatment of neurally-mediated syncope in children and adolescents over the past 30 years: A single center study

Abstract: BackgroundSyncope is the primary cause of transient loss of consciousness, which causes severe physical and mental burdens to children and adolescents.ObjectiveThe study was designed to analyze the spectrum of underlying diseases of syncope and treatment options for neurally-mediated syncope (NMS) in Chinese children and adolescents.MethodsMedical records including history, physical examination, blood biochemistry, standing test, head-up tilt (HUTT), sitting-up test, electroencephalogram (EEG), electrocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Syncope is common in adolescents and the underlying cause is often benign. In rare cases, syncope is caused by life‐threatening cardiac disease or arrhythmia induced by a prescribed drug 5 . Sudden cardiac death is rare in adolescents, seldom related to previous cardiac diseases and often preceded by antecedent and/or prodromal symptoms 6,7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syncope is common in adolescents and the underlying cause is often benign. In rare cases, syncope is caused by life‐threatening cardiac disease or arrhythmia induced by a prescribed drug 5 . Sudden cardiac death is rare in adolescents, seldom related to previous cardiac diseases and often preceded by antecedent and/or prodromal symptoms 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…In rare cases, syncope is caused by lifethreatening cardiac disease or arrhythmia induced by a prescribed drug. 5 Sudden cardiac death is rare in adolescents, seldom related to previous cardiac diseases and often preceded by antecedent and/or prodromal symptoms. 6,7 Although one study reported low risks of psychotropic druginduced adverse cardiac events, 8 individual risks cannot be overlooked.…”
mentioning
confidence: 99%